Development of engine management system for modified diesel engine fuelled by compressed natural gas (CNG) - Ng, Ziet Hong (2009)
Air pollution is a serious global problem. Most country uses diesel engine, which produces substantial amount of emission, for the transportation sector. That is why development of green car is important to solve this problem. Compressed natural gas (CNG) as fuel to run diesel engine is one solution to decrease emission. This thesis deals with the finding of the best air-fuel ratio to be input into the Engine Control Unit (ECU) so that the ECU can manage the engine properly. Simulation of experiment of effect of variable AFR at variable manifold pressure for fixed RPM is run using GT-Power software. Hence a modified single cylinder diesel engine to run on CNG is studied and parameters are taken from the engine to be input into the template library of GT-Power software. In this project, the studied RPM is from 800 RPM to 3000 RPM with increment of 200 RPM. The manifold pressure range from 0.25 Bar to 1.00 Bar with increment of 0.05 Bar. As for the air-fuel ratio (AFR), the range is from 12.5 to 21. The results obtained from the simulation are viewed using GT-Post. The data are then transfer to Microsoft Excel to plot out the graph. From the graph, the best AFR is determined and input into the AFR table of Megatune software and burn into the ECU. Result shows that the engine operate well on lean mixture for all condition. Engine performance curve plotted from the result shows that the trend of curve is the same for all manifold pressure, the only difference is as manifold pressure increase the power output also increases. From published reports and books, it is stated that lean burning of air fuel mixture increases fuel conversion efficiency. Also optimum efficiency from natural gas is obtained when burnt in a lean mixture. It is concluded that the AFR table is successfully inputted with the best AFR at different RPM and manifold pressure.